Evaluation of Four Pulpotomy Techniques in Primary Molars: A Randomized Controlled Trial - Ansari, Ghassem; Morovati, Seyyedeh Pouya; Asgary, Saeed (Iranian Endodontic Journal, 2019)
Introduction: This trial was designed to evaluate the clinical and radiographic success rates of calcium-enriched mixture (CEM) cement with and without low level laser therapy (LLLT) and compare them to that of formocresol (FC) and ferric sulfate (FS) in primary molar pulpotomies. Methods and Materials: This randomized clinical trial was conducted on a total of 160 teeth selected from 40 patients aged 3-9 years. Patients with at least four primary molars needing pulpotomy, were included in order to have each tooth assigned randomly in one of the four following groups; FC, FS, CEM, and LLLT/CEM. Six- and twelve-month follow-up periods were conducted in order to enable a clinical and radiographic evaluation of the treated teeth. Collected data were analyzed using Cochran Q Tests. Results: The 12-month clinical success rate for each technique was: FC=100%, FS=95%, CEM=97.5% and LLLT/CEM=100% with no significant differences (P>0.05). Furthermore, 12-month radiographic success rate for each technique was: FC=100%, FS=92.5%, CEM=95% and LLLT/CEM=100% with no significant differences (P>0.05). Conclusion: Favorable outcomes of four treatment techniques in pulpotomy of primary molar teeth were comparable. CEM with/without LLLT may be considered as a safe and successful pulpotomy treatment modality compared to current conventional methods. Keywords: Calcium-Enriched Mixture; CEM Cement; Ferric Sulfate; Formocresol; Low Level Laser Therapy; Primary Molar; Pulpotomy